Arbuscular mycorrhizal fungi mitigate cadmium stress in maize - Qiqiang Kuang; Yujie Wu; Yamin Gao; Tingting An; Shuo Liu; Liyan Liang; Bingcheng Xu; Suiqi Zhang; Min Yu; Sergey Shabala; Yinglong Chen (Ecotoxicology and Environmental Safety)
Soil cadmium (Cd) pollution poses a significant environmental threat, impacting global food security and human health. Recent studies have highlighted the potential of arbuscular mycorrhizal (AM) fungi to protect crops from various heavy metal stresses, including Cd toxicity. To elucidate the tolerance mechanisms of maize in response to Cd toxicity under AM symbiosis, this study used two maize genotypes with contrasting Cd tolerance: Zhengdan958 (Cd-tolerant) and Zhongke11 (Cd-sensitive). Rhizobox experiments were conducted with and without AM inoculation, alongside Cd treatment. The results revealed that Cd stress severely impaired growth and root development in both genotypes. However, AM symbiosis significantly improved plant height, stem diameter, biomass, root morphology, photosynthetic capacity, nutrient uptake, antioxidant enzyme activity, root Cd content, and concentration, while also reducing lipid peroxidation and shoot Cd accumulation in both genotypes. Notably, AM symbiosis had a more pronounced effect on stem diameter (increased 55 %), root dry weight (118 %), root superoxide dismutase (42 %), and peroxidase activity (209 %), as well as shoot translocation factor (77 %) in Zhongke11 compared to Zhengdan958. Overall, AM symbiosis alleviated Cd toxicity in maize through multiple mechanisms, including enhanced photosynthesis, nutrient uptake, antioxidant defenses, and modulation of Cd transport and accumulation. This study provides valuable insights into the potential application of Cd-tolerant maize genotypes and AM symbiosis for managing Cd-contaminated soils.